Analysis of the Ease of the JKK (Work Accident Insurance) Claim Procedure on Service Satisfaction at BPJS Ketenagakerjaan, Medan Utara Branch - Liska Febrianti; Wahyu Syarvina (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Ease in a procedure is certainly something that everyone really wants. One of them is the convenience in the process of claiming work accident insurance funds. If the claiming process is easy, it will improve the quality of service as expected by the participants of the northern branch of the BPJS Employment. The purpose of this study is to find out the ease of the procedures provided can increase satisfaction with the services provided by the northern branch of the BPJS Employment. This research was conducted with a qualitative descriptive method, by collecting data, interviews, observations and literature review. In the process of claiming the work accident guarantee fund (JKK) of course the northern branch of the BPJS Employment has followed the applicable procedures. This, of course, must be implemented properly and provide convenience for participants to improve the quality of services at the North Medan branch of the BPJS Employment.